The Right to Food and the Planetary Boundaries framework. (1st March 2017) - Heesterman, Wiebina
The 'Right to Food' is a legal entitlement owed to all human beings established in international law more than half a century ago. Fulfilment of the right has been entrusted to states parties to the 1966 International Covenant on Economic, Social and Cultural Rights (ICESCR). However, in practice, the right is often breached because of hostility or indifference from individuals or institutions refusing access to provisions, or because of vicissitudes of nature. Adverse impacts due to human interference in natural processes are increasingly noticeable in the area of food production. These processes have been classified into nine distinct categories, all of which need be kept within certain margins, so-called 'Planetary Boundaries', which delineate a safe operating space for humanity. This paper discusses the impact each of these human-induced developments has on the provision of food as well as the other way round and what the consequences would be if the boundaries were exceeded. Yet there are means of keeping the worst consequences of most of these processes at bay. The paper explores some of these.